Melodies from the Past, Melodies from the Present: Music and Identity in the Cuban Diaspora. - Alfonso, Ivan Darias (Hispanic Research Journal, 2013)
This article discusses the impact of popular music on the Cuban diaspora (London) by focusing on the ways in which music is used to construct notions of identity and nation. It is argued that, in the host country, Cuban emigrants benefit from a diverse soundscape, which enables them to choose, consume, and perform a selection of popular, national, and diasporic music devoid of the political charge music acquired in their homeland. In diaspora, new listening strategies engage migrants in reconsidering the role certain artists had in shaping their previous knowledge about what constituted national music. A new knowledge, produced in diaspora, influences personal processes of subject construction and the appropriation of a national identity, which departs from previous notions learned in the homeland. The article is based on a series of qualitative interviews with members of the Cuban diaspora in London and participant observation carried out during 2006-07. En el presente artículo se discute el impacto de la música popular en la diáspora cubana en Londres enfocándonos en el modo en que la música es utilizada para construir nociones de identidad y nación. Como argumento principal se expone que en el país de acogida los emigrantes cubanos se benefician de un paisaje sonoro diverso que les permite seleccionar, consumir y asumir una selección de música popular, nacional y diaspórica libre de la carga política que éstas adquieren en el país de origen. En la diáspora, a través de nuevas estrategias para escuchar música, los emigrados reconsideran el papel que ciertos artistas tuvieron en conformar su conocimiento sobre lo que constituía música nacional. El nuevo conocimiento, producido en la diáspora, influye ahora en procesos personales de construcción y apropiación de la identidad nacional que se diferencian de las nociones previas de identidad aprendidas en Cuba. El artículo se basa en una serie de entrevistas informales y observación llevadas a cabo durante 2006 y 2007 en Londres.